Evaluating working memory: Comparing change-detection tasks and Wechsler working memory subtests in school-age children. Issue 7 (9th August 2017) - Colbert, Alison; Bo, Jin
ABSTRACT: Among a number of methods for assessing working memory (WM), span tasks have been commonly utilized in clinical psychology, whereas change-detection tasks are often used in experimental or cognitive psychology. This study sought to understand the use of change-detection tasks in children and to evaluate the relationship between change-detection tasks and clinical WM measures in the Wechsler Intelligence Scale for Children, Fourth Edition (WISC–IV). Results revealed that the overall pattern of performance in change-detection tasks for children was similar to adults' performance in the literature; with increased array size, response accuracy systematically decreased. Significant age-related improvements on visuospatial and verbal WM capacities were found in school-age children. Although WISC–IV WM measures were significantly correlated with each other, only the Arithmetic subtest was significantly correlated with visuospatial WM as measured by the change-detection task, and none were significantly correlated with verbal WM as measured by the change-detection task. These results suggest the clinical WISC–IV WM subtests may not elicit the same construct as experimental change-detection WM measures, with the possible exception of the Arithmetic subtest.